(untitled) (Research, Society and Development, 2022)
Objective: To know the difficulties of teachers in the use of active methodologies in the teaching-learning process of their students in the Bachelor of Medicine course. Method: A descriptive and cross-sectional study was carried out, with a quali-quantitative character, approved by the Ethics Committee of the Centro Universitário da Amazônia. Data collection was performed using an electronic form for tutors from the 1st to the 8th period of a private University Center in Northern Brazil. Results: Of the 41 tutors from the 1st to the 8th period, 28 answered the form, giving us a sample of 68.29% participation. Where 92.86% were graduated using the traditional method; 67.86% graduated in medicine who work for 7 years or more as teachers. As for the difficulties perceived in opening and closing problems in the tutorial sessions, 50% have difficulties in brainstorming, leaving the superficial discussion and 67.86% have low power of synthesis, consecutively. Conclusion: The difficulties faced by teachers point to the need for a national effort for professional updating, as well as the need for greater investment in research that focuses on the theme, based on the recognition of its importance and the existing scientific gap.